Job crafting amongst the Thai workforce: The influences of occupational future time perspective, age, and proactive personality - Lerthirunvibul, Ponpicha; Sutaputra, Pongpol; Tanongsakmontri, Natanat; Jarunratanakul, Prapimpa (Kasetsart Journal of Social Sciences, 2023)
Previous research suggests that occupational future time perspective (OFTP), age, and proactive personality (PP) are significantly positively linked to proactive behaviors, (for instance, job search intensity). Our cross-sectional correlational study explored the variables in the context of job crafting (JC), another motivation-driven occupational behavior. Our study extended the existing research on PP and OFTP (i.e., Zacher, 2013) in the context of job crafting. We distributed online surveys which contained JC, PP, and OFTP scale items, collecting data from 155 full-time employees within organizations in Thailand. With JC, employees modify their job interms of work tasks, cognitions, and relationships to satisfy demands. Thus, our study aimed to examine the relationships between PP, OFTP, and age, and their influences on JC. We found that a PP was positively related to JC (H1). The relationship between age and JC was inconsistent with our prediction, showing a nonsignificant, and positive relationship with JC (H2). Furthermore, age did not moderate the PP-JC relationship (H3, H5). OFTP was also found to mediate the age-JC relationship (H4). Our findings provide better understanding of the factors influencing JC and the similarities to and differences from job search intensity, another self-initiated behavior, which may inform interventions for improving occupational outcomes.